2015
DOI: 10.18054/pb.2015.117.3.3090
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of gene FanC-2NT encoding K99-2NT fimbrial antigen of enterotoxigenic Escherichia coli from diarrheic post-weaning piglets

Abstract: Background and Purpose: The K99 (F5) is one pilus adhesin that mediates the attachment of enterotoxigenic E. coli (ETEC) strains to small intestines to cause to diarrhea in piglets IntroductIonT he K99 (F5) is one pilus adhesin that mediates the attachment of enterotoxigenic E. coli (ETEC) strains to small intestines to cause to diarrhea in piglets, lambs and newborn calves (1). The ETEC enters the small intestine and binding to the specific receptors on the surface of epithelial cells through the K99 (2). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…BL21 (DE3) cells on YJ culture medium with 0.5 mM IPTG induction, after analyzed through SDS-PAGE has been shown in Fig 4. The protein bands of three repeats transformed E. coli cells with 0.5 mM IPTG induction after 5h (lane 1, 2 and 3) from SDS-PAGE gel as shown in Fig 4 revealed that the expression of recombinant DHDPS polypeptides in E. coli. BL21 (DE3) cells on YJ culture medium was expected to produce proteins of 37.2 kDa (33.5 kDa DHDPS subunit (Fig 3), and 3.7 kDa fusion fragment of the pET200/D-TOTO vector, (Loc et al, 2015). For the transformed E. coli cells without IPTG induction, a weak protein band of expected sizes were observed (Fig 4, NC), suggesting that induction with IPTG is necessary for optimizing the expression of DHDPS2 subunit gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BL21 (DE3) cells on YJ culture medium with 0.5 mM IPTG induction, after analyzed through SDS-PAGE has been shown in Fig 4. The protein bands of three repeats transformed E. coli cells with 0.5 mM IPTG induction after 5h (lane 1, 2 and 3) from SDS-PAGE gel as shown in Fig 4 revealed that the expression of recombinant DHDPS polypeptides in E. coli. BL21 (DE3) cells on YJ culture medium was expected to produce proteins of 37.2 kDa (33.5 kDa DHDPS subunit (Fig 3), and 3.7 kDa fusion fragment of the pET200/D-TOTO vector, (Loc et al, 2015). For the transformed E. coli cells without IPTG induction, a weak protein band of expected sizes were observed (Fig 4, NC), suggesting that induction with IPTG is necessary for optimizing the expression of DHDPS2 subunit gene.…”
Section: Resultsmentioning
confidence: 99%
“…BL21 (DE3) cells have been shown in Fig 7. In fact, LB is one of the normal culture media to use for determining the expression of the recombinant general protein in E. coli. BL21 (DE3) cells (Loc et al, 2015, Ellen et al, 2013, Miksch et al, 2008. LB culture medium was also applied to detect the expression of recombinant general protein in E. coli.…”
Section: Resultsmentioning
confidence: 99%